Practicing Diplomacy: Perspectives, Applications, and Simulations - Enverga, Manuel R, III (Archīum Ateneo, 2019)
As a result of globalization; states have sought new ways of asserting control over the rapid flow of goods; people; capital; and ideas; which move across their borders. For example; one of the World Trade Organization___s (WTO) functions is to regulate tari barriers erected by individual states. Governments have also found it necessary to establish mechanisms for managing collaborative activities that are international in nature. Climate change agreements and the establishment of the International Space Station would not have been possible without these instruments; which are enforced through binding treaties; negotiated by diplomats; and continue to be enforced by specialists who possess diplomatic skills. These standardised norms of behaviour increasingly govern seemingly mundane aspects people's lives; and they only function through a diplomatic infrastructure.